Characterization of electro-mechanical response in novel carbon fiber composite materials. (August 2019) - Sherman, Riley; Chalivendra, Vijaya; Hall, Asha; Haile, Mulugeta; Nataraj, Latha; Coatney, Michael; Kim, Yong
A comprehensive experimental parametric study is performed to investigate the electro-mechanical response of novel three-dimensional conductive multi-functional carbon/epoxy composite materials. Three-dimensional conductive network is generated by embedding multi-wall carbon nanotubes in the epoxy matrix and reinforcing short carbon fibers between the carbon fabric laminates. An open mold compression method is utilized to fabricate the composite materials. Wet electro-up-flocking technology is employed to reinforce 150-µm and 350-µm length carbon fibers vertically at varying densities (500, 1000, 1500, 2000 fibers/mm 2 ) between each laminate to analyze the effects these parameters have on electrical resistivity, tensile properties, and electro-mechanical response to quasi-static tensile loading. A high-resolution four-point circumferential ring probe is used to obtain electrical measurements. The resistivity of the composites having 150 µm flocked carbon fibers did not show significant change with increase in flock density; however, composites of 350-µm length carbon fibers showed a clear decrease in resistivity by a factor of 10 when the flock density increased from 500 to 2000 fibers/mm 2 . The electro-mechanical response of composites without short carbon fibers is inconsistent and jagged compared to that of flocked composites. The composites having 350-µm long carbon fibers showed a longer duration of initially decreasing resistance due to the applied tensile load when compared to that of 150 µm flocked carbon fibers. However, composites with no short carbon fibers registered maximum value of percentage change in resistance at the break point of tensile loading.